IMPLEMENTASI MANAJEMEN MUTU TERPADU DALAM MENINGKATKAN PROFESIONALISME GURU DI SD ISLAM ROUSHON FIKR PULO, JOMBANG - Laily Masruroh; Sholihul Anshori; Jasminto (EL-Islam, 2019)
Some focus of the research are (1) Implementation of Integrated Quality Management in Improving Teacher Professionalism at Islamic Elementary School Roushon Fikr Pulo, Jombang (2) factors of supporting and inhibiting Integrated Quality Management Implementation in Improving Teacher Professionalism at Islamic Elementary School Roushon Fikr Pulo, Jombang. The purpose of discussing the main issues in writing the operational design of this paper is to escribe (1) Implementation of Integrated Quality Management in Improving Teacher Professionalism at Islamic Elementary School Roushon Fikr Pulo,Jombang (2) factors of supporting and inhibiting Integrated Quality Management Implementation in Improving Teacher Professionalism at Islamic Elementary School Roushon Fikr Pulo, Jombang. School as educational institutions is a place for educational processes that can be carried out by having a complex and dynamic system. The core activity of the school is HR (Human Resource) management. Preparation of quality human resources can be achieved only with quality education as well. All components of the education system (input, output process, outcome) must require some certain quality standards. An organization can improve and maintain its quality by building a quality improvement system, one of the quality improvement system models is TQM, Total Quality Management / Integrated Quality Management (MMT). TQM is based on customer satisfaction as the main target. Customers can be divided into internal customers and external customers. In education, internal customer is a system or doer of the educational institution itself, for example, the principal, teachers, staff, and school organizers. The researcher used a type of qualitative field research (field research) that was descriptive. The researcher used the method of observation (observation), interviews (interviews), focused discussions and documentation to collect the data.In the study, it was found that the quality of teachers in Islam Roushon Fikr was a well-chosen and well-selected teacher. To find out the level of teacher professionalism can be seen through the level of education, understanding of teacher competence, upgrading or training, and teacher competency testing. The implementation of MMT in increasing teacher professionalism is among others through teacher recruitment so, the selected teachers are skilled and creative teachers. Factors of supporting the implementation of TQM in increasing teacher professionalism are influenced by the leadership style of the principal and all supporting structures at the school. Factors of inhibiting the implementation of TQM in improving the teacher professionalism, we can say it is very little even not at all because of good performance, commitment and enjoyable environment. To realize it, the principal tried to create a healthyand pleasant work atmosphere by improving and maintaining togetherness in the group.